2021
DOI: 10.3390/nu13020621
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nutritional Interventions on Long-Term Patient Survival in Advanced Chronic Kidney Disease

Abstract: Patients with end-stage kidney disease (ESKD) are at high risk of malnutrition and subsequent related mortality when starting dialysis. However, there have been few clinical studies on the effect of nutritional interventions on long-term patient survival. A 2-year longitudinal study was conducted from January 2012 to December 2016. A total of 186 patients with non-dialysis ESKD started the nutritional education program (NEP), and 169 completed it. A total of 128 patients participated in a NEP over 6 months (pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…They found that the amount of inorganic P ingested was associated with the ratio of urinary P to urea nitrogen excreted (P/UUN ratio), but that the amount of P ingested from animal and vegetable sources was not associated with the P/UUN ratio in 24 h urine samples [ 10 ]. Thus, the P/UUN ratio in 24 h urine samples may be a useful means of estimating inorganic P intake [ 11 ]. This finding may help in the management of mineral bone disorder in patients with CKD, in which the estimation and control of serum P concentration are important.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…They found that the amount of inorganic P ingested was associated with the ratio of urinary P to urea nitrogen excreted (P/UUN ratio), but that the amount of P ingested from animal and vegetable sources was not associated with the P/UUN ratio in 24 h urine samples [ 10 ]. Thus, the P/UUN ratio in 24 h urine samples may be a useful means of estimating inorganic P intake [ 11 ]. This finding may help in the management of mineral bone disorder in patients with CKD, in which the estimation and control of serum P concentration are important.…”
mentioning
confidence: 99%
“…Perez-Torres et al demonstrated the long-term (2-year) effects of a nutritional intervention, referred to as a nutritional educational program, in 186 patients with advanced CKD [ 11 ]. This nutritional educational program consisted of an individualized diet plan based on each patient’s initial nutritional status, four nutritional education sessions, a nutritional assessment, and 6 months of monitoring [ 11 ].…”
mentioning
confidence: 99%
See 3 more Smart Citations